SELEKSI KLON-KLON UBIJALAR DENGAN KANDUNGAN BETAKAROTEN DAN KANDUNGAN PATI TINGGI - Nasdeko, Gandha; Lestari, Sri Umi; Sutoyo, Sutoyo (Universitas Tribhuwana Tunggadewi, 2019)
The aim of this study was to evaluate the beta-carotene content, starch content and % of dried tuber ingredients in several new sweet potato clones. The clones consisted of five new clones and compared to three control cultivars. A randomized block design with three replications was used in this study, carried out in an experimental unit measuring 3 m x 0.6 m in single row. Each experimental unit was planted with 25 cm long cassava cuttings, spacing in 25 cm in a row. Phonska fertilizer with a dose of 300 kg/ha is given twice, first at 7 days after planting (dap) as many as 1/3 parts and the rest given at plant age 45 days. Plants were harvested at 4 months of growh duration and were observed based on component parameters of yield, Harvest Index, total carotene and starch content. The results showed that the performance of total carotene in the five clones evaluated ranged from 0.50 - 75.26 µg/g, the starch content ranged from 9.66 - 18.52% based on fresh weight, and the dry matter content of the storage root ranged from 23.17% - 34.06%. Two new sweet potato clones (Beta 2-♀-12 and Beta 2-♂-22) had total carotene levels exceeding their control cultivars, respectively 52.83 and 75.26 µg/g; the starch content is 18.30% and 10.57% based on the wet weight of the tuber. The starch content was positively correlated (r = 0.875) with the dry matter of tuber (% dry matter); on the contrary the level of total carotene to starch content and % dry matter in all the clones had a negative correlation of -0.614 and -0565 respectively. Tujuan penelitian ini untuk mengevaluasi kandungan betakaroten, kadar pati dan % bahan kering umbi pada beberapa klon ubijalar baru. Klon yang dievaluasi terdiri lima klon baru dan dibandingkan dengan tiga kultivar kontrol. Rancangan acak kelompok dengan tiga ulangan digunakan dalam penelitian ini, dikerjakan pada unit percobaan berukuran 3 m x 0.6 m secara single row. Setiap unit percobaan ditanami stek ubijalar berukuran panjang + 25 cm, jarak tanam dalam baris 25 cm. Pupuk dasar Phonska dengan dosis pupuk 300 kg/ha diberikan dua kali, pertama pada umur 7 hari setelah tanam (hst) sebanyak 1/3 bagian dan sisanya diberikan pada umur tanaman 45 hst. Tanaman dipanen pada umur 4 bulan dan diamati berdasarkan parameter komponen hasil, Indeks Panen, kadar total karoten dan kadar pati. Hasil penelitian menunjukkan bahwa keragaan kadar total karoten pada lima klon yang dievaluasi berkisar antara 0.50 – 75.26 µg/g, kadar patinya berkisar antara 9.66 – 18.52 % berdasar bobot basah umbi, dan kadar bahan kering umbinya berkisar antara 23.17 % – 34.06 %. Dua klon ubijalar baru (Beta 2-♀-12 dan Beta 2-♂-22) memiliki kadar total karoten melebihi kultivar kontrolnya, masing-masing sebesar 52.83 dan 75.26 µg/g; kadar patinya sebesar 18.30 % dan 10.57 % berdasar bobot basah umbinya. Kadar pati berkorelasi positif dengan kadar bahan kering umbi (% BK umbi) dengan nilai korelasi r = 0.875; sebaliknya kadar kadar total karoten terhadap kadar pati dan % BK umbi pada semua klon yang dievaluasi memiliki korelasi negatif masing-masing sebesar ─ 0.614 dan ─ 0565.